Mapping of DMP stakeholders and user needs in the project 'Data Management Plans: Support package for Norwegian higher education libraries' - Ostrop, Jenny; Kvale, Live Håndlykken; Heggland, Ingrid; Høier, Svein; Longva, Leif; Bösl, Korbinian (Zenodo, 2024)
The project Data Management Plans: Support package for Norwegian higher education libraries aims to create a comprehensive Data Management Plan (DMP) support package with resources and guidance both for users and support personnel at Norwegian research institutions. Thereby the project follows up on recommendations on establishing a common understanding of DMP requirements and aligning DMP guidance between institutions from a collaborative DMP project by the University libraries in Bergen, Oslo, Trondheim and Tromsø published in December2022 . To establish a common ground for defining DMP outlines and guidance, the project group has conducted a mapping of DMP stakeholders in Norway. This mapping is both inspired by taking a multi-stakeholder perspective on data management plans as proposed by Kvale and Pharo and the group’s extensive experience in providing data management support in institutions and research infrastructures to both researchers and policy makers. Furthermore, the project group has categorised aspects that a DMP may have to cover as different researchers and research projects can have opposing needs. In order to provide relevant guidance, the whole spectrum should be considered. Writing a DMP contributes to making data and other outputs of research projects FAIR. Eventually, if certain prerequisites are met, the DMP itself can be considered a research object and be integrated in the Open Science ecosystem. Defining these premises was valuable for the ongoing project work. We invite the research data community to provide feedback.